Establishment of the Asia Oncology Nursing Society (AONS) - Kazuko Onishi (Asia-Pacific Journal of Oncology Nursing, 2014)
Over the past several years, whenever an informal group of Asian oncology nurses gathered, they talked about their mutual desire to create an organization closer to their homes that would be similar to the European Oncology Nursing Society (EONS). They saw this as a means for more of their colleagues to learn about the latest in cancer nursing and to have a time and place to network among themselves. This message continued to gain strength whenever these nurses met at other international meetings such as the International Conference on Cancer Nursing (ICCN), the Multinational Association of Supportive Care in Cancer (MASCC) and the Oncology Nursing Society in US. A definite and planned step toward forming an Asian organization as the first meeting was taken on June 24 2011 when several Asian nurses were attending a MASCC meeting in Greece. The second meeting was held in Prague, Czech Republic, in conjunction with the 17 th ICCN meeting on September 10 2012, where the participants of the meeting included 21 oncology nurses from Asian countries. Finally, the first official meeting of the board directors from nine countries was held on November 21 2013 in Bangkok, Thailand. Now, and in the future, sharing and collaborating in the practice, education and research for oncology nursing in Asia is needed.